2014
DOI: 10.14202/vetworld.2014.738-743
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic residues in broiler and layer meat in Chittagong district of Bangladesh

Abstract: The present study was described thin layer chromatography (TLC) and ultra-high performance liquid chromatography (UHPLC) method for the detection of antibacterial substances in poultry muscle (breast and thigh), kidney, and liver.Materials and Methods: TLC method was used for screening detection of tetracycline, amoxicillin, ciprofloxacin, and enrofloxacin residues in poultry tissues. The samples were extracted with trichloroacetic acid (30%), diethyl ether, followed by detection in pre-coated TLC paper on ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
70
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 15 publications
20
70
3
Order By: Relevance
“…Among the known genetic mechanisms of such antimicrobial resistance include the horizontal transfer of multiple resistant genes, often found tandemly located in large mobile elements (e.g., plasmids, Class I integron, conjugative transposon) in the bacterial genome and mutations in genes, including gyrA and gyrB of DNA gyrase and parC and parE of topoisomerase IV, regulating efflux pump systems and insertional modulation in cmeB gene inactivating the CmeABC multidrug efflux pump [46]. The presence of residual content of antimicrobials in most of the tested poultry meat and liver samples in this study is similar to observations reported from another region in Bangladesh [21]. The higher occurrence of such contamination in liver tissue than meat samples (Table 3) is in accordance with their biological processing within poultry animal.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among the known genetic mechanisms of such antimicrobial resistance include the horizontal transfer of multiple resistant genes, often found tandemly located in large mobile elements (e.g., plasmids, Class I integron, conjugative transposon) in the bacterial genome and mutations in genes, including gyrA and gyrB of DNA gyrase and parC and parE of topoisomerase IV, regulating efflux pump systems and insertional modulation in cmeB gene inactivating the CmeABC multidrug efflux pump [46]. The presence of residual content of antimicrobials in most of the tested poultry meat and liver samples in this study is similar to observations reported from another region in Bangladesh [21]. The higher occurrence of such contamination in liver tissue than meat samples (Table 3) is in accordance with their biological processing within poultry animal.…”
Section: Discussionsupporting
confidence: 88%
“…Since a few studies have observed the occurrence and antibiotic susceptibility patterns of Campylobacter spp. in poultry farms, detection of antimicrobial residues, together with socio-environmental risks prevailing in poultry farming and LBMs in Bangladesh have not been adequately explored [20,21] .…”
mentioning
confidence: 99%
“…Among the known genetic mechanisms of such antimicrobial resistance include the horizontal transfer of multiple resistant genes, often found tandemly located in large mobile elements (e.g., plasmids, Class I integron, conjugative transposon) in the bacterial genome and mutations in genes, including gyrA and gyrB of DNA gyrase and parC and parE of topoisomerase IV, regulating efflux pump systems and insertional modulation in cmeB gene inactivating the CmeABC multidrug efflux pump [37]. The presence of residual content of antimicrobials in most of the tested poultry meat and liver samples in this study is similar to observations reported from another region in Bangladesh [13]. The higher occurrence of such contamination in liver tissue than meat samples (Table 3) is in accordance with their biological processing within poultry animal.…”
Section: Large-scale Application Of Antimicrobials As Human and Vetersupporting
confidence: 84%
“…In contrast, the examined samples of meat and kidney were accepted where their OTC residue was within the permissible l Salehzadeh et al (2006) who recorded that the positive samples showed MRLs 27.77%, 95.55% and (18.88%) in muscles, liver and kidney samples, respectively, Olatoye and Ehinmowo (2009), Hussein and Khalil (2013) , Hosnia et al (2015) and El-Bagory et al (2016) who recorded that the positive samples showed 55%,70% and 70% of the examined samples of local broilers meat, liver and kidneys were positive However, lower results were reported by Sattar et al (2014), Sewond et al (2014) and Lara et al (1992) who recorded that the levels of OTC residues (ug/g) ranged from 0.012 -0.014µg ∕ g in chicken meat samples.…”
Section: The Incidence Of Oxytetracycline Residues In the Examined Samentioning
confidence: 94%